Targeting Metabolic Deregulation Landscapes in Breast Cancer Subtypes - Serrano-Carbajal, Erandi A.; Espinal-Enríquez, Jesús; Hernández-Lemus, Enrique (Frontiers in Oncology, 2020)
Metabolic deregulation is an emergent hallmark of cancer. Altered patterns of metabolic pathways derive in exacerbated synthesis of macromolecules, increased proliferation, and resistance to treatment via alteration of drug processing. In addition, molecular heterogeneity generates a barrier for therapeutic options. As is the case, this broad variance in molecular metabolism in breast cancer constitutes simultaneously, a source of prognostic and therapeutic challenges and a door conducing to novel interventions. In this work, we investigated the metabolic deregulation landscapes in breast cancer molecular subtypes. Such landscapes are the regulatory signatures behind subtype-specific metabolic features. n= 735 breast cancer samples of the Luminal A, Luminal B, Her2+ and Basal subtypes, as well as n= 113 healthy breast tissue samples were analyzed. By means of a single-sample-based algorithm, deregulation for all metabolic pathways in every sample was determined. Deregulation levels match almost perfectly with the molecular classification, indicating that metabolic anomalies are closely associated with gene expression signatures. Luminal B tumors resulted the most deregulated but are also the ones with higher within-subtype variance. We argued that this variation may underlie the fact that Luminal B tumors usually present worst prognosis, a high rate of recurrence, and the lowest response to treatment in the long term. Finally, we designed a therapeutic scheme to regulate purine metabolism in breast cancer, independently of the molecular subtype. Such scheme is founded on a computational tool that provides a set of FDA-approved drugs to target pathway-specific differentially expressed genes. By providing metabolic deregulation patterns at the single-sample-level in breast cancer subtypes, we have been able to further characterize tumor behavior. This approach, together with targeted therapy may open novel avenues for the design of personalized diagnostic, prognostic and therapeutic strategies.